2017
DOI: 10.17059/2017-1-24
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Planning and Policy Evaluation in an Urban Conurbation: a Regional Agent-Based Economic Model

Abstract: 1 This paper studies different functions and relations between 45 agglomerated municipalities in southern Switzerland (Ticino), using a territorial agent-based model. Our research adopts a bottom-up approach to urban systems, considering the agglomeration mechanism and effects of different regional and urban policies, and simulates the individual actions of diverse agents on a real city using an Agent-based model (ABM). Simulating the individual actions of diverse agents on a real city and measuring the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The debate on the formation of multiclusters and the insufficient development of methods (Kireeva, 2015) and tools for evaluating the effectiveness of cluster development (Achenbach, 2012) as an institutional phenomenon (Stricker & Baruffini, 2017) and the main form of integration of the Russian industry predetermined the need for this study. In modern conditions, the formation and development of clusters is a promising direction for improving the competitiveness of the national economy.…”
Section: Sectoral Characteristics Of Innovative Clustermentioning
confidence: 99%
“…The debate on the formation of multiclusters and the insufficient development of methods (Kireeva, 2015) and tools for evaluating the effectiveness of cluster development (Achenbach, 2012) as an institutional phenomenon (Stricker & Baruffini, 2017) and the main form of integration of the Russian industry predetermined the need for this study. In modern conditions, the formation and development of clusters is a promising direction for improving the competitiveness of the national economy.…”
Section: Sectoral Characteristics Of Innovative Clustermentioning
confidence: 99%
“…Authors Auteri and Constantini [14], who dealt with the analysis of the impact of public investments and transfers to individual regions in Italy, concluded that, unlike transfers, public investments have a positive effect on economic growth. Tax advantageous locations in terms of regions of southern Switzerland examined Stricker and Baruffini in their study [15]. Tax revenues as part of the quantitative indexes were analyzed by Andreeva et al [16], while examining the impact of the institutional factor on the development of regional international economic relations.…”
Section: Theoretical Basesmentioning
confidence: 99%